Toughened modified polylactic acid material and preparation method thereof
By mixing polystumin and other materials through the mixing method, prepare tougher and modified polystumin materials, solve the problem of insufficient brittleness and toughness of polymaphinic acid materials, realize significant toughened and obstructive resistance, broaden Its scope of use in industrial and medical applications.
Patent Information
- Application Number
- CN202411713617.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-24
AI Technical Summary
Polylactic acid materials have problems such as high brittleness, poor toughness, lack of elasticity, general fluidity and slow degradation speed, which limits their use in industrial and medical applications.
Polymine is mixed with polylactal acid with Mongolian soil, polycoline, dihydrams, and oxide, and prepares tougher and modified polystumin materials. By careful design and selection of specific raw materials ratio, this method ensures that each raw material plays the best coordinated role in the mixture, and improves the mechanical properties and blocking performance of the material.
The significant tougher effect of polystumin materials has been achieved, and its breakdown rate, stretch strength, and stretching elastic modulus are improved. And widely applicable.
Smart Images

Figure BDA0005156373740000021 
Figure BDA0005156373740000022 
Figure BDA0005156373740000032
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new materials, and in particular to a toughened and modified polylactic acid material and a preparation method thereof. Background Art
[0002] Polylactic acid (PLA) is a high molecular polymer made from green plants. It is made by decomposing the raw materials into glucose, fermenting them to generate lactic acid, and polymerizing the lactic acid. Its physical and chemical properties are similar to those of traditional thermoplastics. However, compared with traditional plastics, it has better biodegradability and will not cause pollution and damage to the environment, solving the energy consumption and environmental pollution problems caused by the processing of traditional plastics.
[0003] In addition to its excellent biodegradability, PLA's good processability and good mechanical properties have led to its extensive research and application. In the biomedical field, PLA can be used to produce disposable medical tools, which can reduce environmental pollution after disposal. Because of its certain biocompatibility and mechanical strength, it can be used to manufacture non-removable surgical sutures and artificial bone tissue. However, PLA materials have problems such as high brittleness, poor toughness, lack of elasticity, general fluidity and slow degradation. These defects limit many industrial applications of PLA, especially industrial and medical applications that require good plastic deformation capabilities under high stress levels. Therefore, in order to further broaden the scope of application of PLA, it is necessary to perform appropriate physical or chemical modifications on it so that it can meet different usage requirements.
[0004] There are many PLA modification schemes in the prior art, such as:
[0005] Chinese patent CN110204876A discloses a modification method for strengthening and toughening polylactic acid. The polylactic acid material is modified by melt blending a sulfonated polystyrene ionomer containing a sulfonated rigid segment and a thermoplastic elastic flexible segment with polylactic acid, and the strengthening and toughening effect is achieved at the same time. Sulfonated polystyrene ionomers are polystyrene block copolymers such as poly (styrene-butadiene-styrene) (SEBS) and the like, obtained by sulfonating polystyrene segments to varying degrees, wherein the flexible segments play a role in toughening the polylactic acid composite material.
[0006] Chinese patent CN102675523B discloses a polylactic acid toughening agent and a preparation method thereof, a modified polylactic acid and a preparation method thereof, wherein the preparation method of the polylactic acid toughening agent comprises the following steps: (1) adding methyl acrylate and polymethyl methacrylate to a first emulsifier to obtain a first mixture; (2) adding a first initiator to the first mixture to initiate a reaction, removing the condensate generated in the reaction, and obtaining a second mixture; (3) adding a second emulsifier to the second mixture, and then adding a third mixture, wherein the third mixture is composed of methyl acrylate, a dispersant, a second emulsifier, a second initiator and water, and continuing the reaction to obtain an emulsion; (4) diluting the emulsion, adding a demulsifier, heating and coagulating, and drying the precipitate to obtain a polylactic acid toughening agent. The preparation method is simple, the prepared polylactic acid toughening agent has good compatibility with polylactic acid, and the amount of additives used in the modified polylactic acid obtained therefrom is reduced, thereby improving the utilization rate of polylactic acid.
[0007] Among them, blending is a common method for polymer modification, which has the advantages of simple method, low cost and easy operation. Blending modification of polylactic acid can make PLA obtain more ideal comprehensive properties and greatly broaden the application range of polylactic acid. In order to improve the toughening efficiency of polylactic acid, more polylactic acid toughening methods need to be further developed. Summary of the invention
[0008] The object of the present invention is to provide a toughened modified polylactic acid material and a preparation method thereof, which has excellent mechanical properties and barrier properties.
[0009] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0010] The present invention provides a toughened modified polylactic acid material, which is made of the following raw materials in parts by weight:
[0011]
[0012] Preferably, it is made from the following raw materials in parts by weight:
[0013]
[0014]
[0015] The present invention also provides a method for preparing the toughened and modified polylactic acid material, comprising the following steps:
[0016] All materials are blended to obtain toughened modified polylactic acid material.
[0017] Preferably, the blending is performed by melt blending.
[0018] Preferably, the equipment used in the melt blending method is an internal mixer.
[0019] Preferably, the temperature of the melt blending method is 150-250°C.
[0020] Preferably, the melt blending process is carried out for 10 to 30 minutes.
[0021] Preferably, the rotation speed of the melt blending method is 50 to 100 rpm.
[0022] Preferably, the blending further comprises extrusion molding;
[0023] The thickness of the extrusion molding is 0.05 to 10 mm.
[0024] The present invention also provides the use of the toughened modified polylactic acid material or the toughened modified polylactic acid material prepared by the above preparation method in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing.
[0025] Technical effects and advantages of the present invention:
[0026] The polylactic acid material of the present invention has excellent performance, with significant elongation at break, excellent tensile strength and high tensile elastic modulus. In addition, the material has also successfully achieved a significant improvement in barrier properties, making it more practical and widely applicable in various applications. DETAILED DESCRIPTION
[0027] The present invention provides a toughened modified polylactic acid material, which is made of the following raw materials in parts by weight:
[0028]
[0029] Preferably, it is made from the following raw materials in parts by weight:
[0030]
[0031]
[0032] In the present invention, the polylactic acid, also known as polylactide (PLA), is a polyester polymer obtained by polymerization with lactic acid as the main raw material. It is a new type of biodegradable material with good solvent resistance and can be processed in a variety of ways, such as extrusion, spinning, biaxial stretching, and injection blow molding. In addition to being biodegradable, the products made of polylactic acid have good biocompatibility, gloss, transparency, feel and heat resistance. The polylactic acid used in the embodiment of the present invention is in liquid form, CAS No.: 26023-30-3, purchased from Bashifu (Shanghai) Biomedical Technology Co., Ltd.
[0033] In the present invention, the montmorillonite is also known as colloid stone and microcrystalline kaolinite, a natural mineral of silicate, and is the main mineral component of bentonite ore. Monoclinic system, multi-position microcrystals, aggregates are earthy, spherical, etc. White with a slight gray, light yellow, light green, light blue when containing impurities, earthy luster or matte, slippery. After adding water, its volume can expand several times and become a paste. After being heated and dehydrated, the volume shrinks. It has strong adsorption capacity and cation exchange performance, and is mainly produced in the weathering crust of volcanic tuff. Montmorillonite (including calcium-based, sodium-based, sodium-calcium-based, magnesium-based montmorillonite) is dispersed through exfoliation, purified and modified, ultra-fine graded, and specially organically composited, with an average chip thickness of less than 25nm, and can be used as a bleaching agent, adsorbent filler, and is called a "universal material". The montmorillonite used in the embodiment of the present invention is purchased from the market.
[0034] In the present invention, the polycaprolactone is an organic high molecular polymer with the chemical formula (C6H 10 O2) n , which has the property of being well soluble in aromatic compounds, ketones and polar solvents. It is prepared by ring-opening polymerization of ε-caprolactone under the conditions of metal organic compounds (such as tetraphenyltin) as catalyst and dihydroxy or trihydroxy as initiator. It belongs to polymerized polyester, and its molecular weight and disproportionation degree vary with the type and amount of starting materials. The PCL raw material used in the embodiment of the present invention is in the form of translucent plastic particles, which is a blown film extrusion grade product purchased from Dongguan Baojia Plastic Co., Ltd.
[0035] In the present invention, diethanolamine (DEA), also known as 2,2'-dihydroxydiethylamine, is an organic compound with a chemical formula of C4H 11 NO2. The experiments related to the embodiments of the present invention were carried out under the laboratory safety supervision and management regulations.
[0036] In the present invention, the propylene oxide, also known as propylene oxide, methyl ethylene oxide, 1,2-propylene oxide, is an organic compound with a chemical formula of C3H6O. It is a very important organic compound raw material and the third largest propylene derivative after polypropylene and acrylonitrile. Propylene oxide is a colorless ether-flavored liquid with a low boiling point, flammable, and chiral. Industrial products are generally racemic mixtures of two enantiomers. It is partially miscible with water and miscible with ethanol and ether. It forms a binary azeotropic mixture with pentane, pentene, cyclopentane, cyclopentene, and dichloromethane; the propylene oxide used in the embodiment of the present invention is a colorless liquid with a CAS number of 75-56-9. The manufacturer is Jinan Huiteng, and the relevant experiments are carried out under the laboratory safety supervision and management regulations.
[0037] In the present invention, the polymethyl methacrylate (PMMA), referred to as PMMA, is a high molecular polymer, also known as acrylic or organic glass, with high transparency, low price, easy mechanical processing and other advantages, and is a commonly used glass substitute. The mechanical strength of PMMA is relatively high: the relative molecular mass of PMMA is about 2 million, it is a long-chain high molecular polymer, and the chain forming the molecule is very soft, so the strength of PMMA is relatively high, and the tensile and impact resistance is 7 to 18 times higher than that of ordinary glass. The PMMA treated by stretching can be used as bulletproof glass, and also as a canopy on military aircraft, etc.; PMMACAS No.: 9011-14-7 used in the embodiment of the present invention was purchased from Shandong Guohua Chemical Co., Ltd., and the relevant experiments were carried out under the laboratory safety supervision and management regulations.
[0038] In the present invention, by carefully designing and selecting a specific raw material ratio, the optimal performance of the toughened modified polylactic acid blend can be effectively achieved. This ratio ensures that the various raw materials can play the best synergistic role in the blend, thereby achieving the expected material performance. Specifically, the amount of each raw material is accurately calculated to ensure that their proportion in the blend is just right. If the amount of some of the raw materials is too high, some performance of the blend may be reduced, or even incompatible, thereby affecting the overall performance of the material. On the contrary, if the amount of some raw materials is too low, they may not be able to fully play their due role, resulting in the performance of the blend failing to reach the optimal state. Therefore, only under the premise of strictly controlling the amount of raw materials, can it be ensured that the blended material in the present invention can show excellent effects and meet various application requirements.
[0039] The present invention also provides a method for preparing the toughened modified polylactic acid material, comprising the following steps: all materials are blended to obtain a toughened modified polylactic acid material. Preferably, the blending adopts a melt blending method. Preferably, the equipment used in the melt blending method is an internal mixer. Preferably, the temperature of the melt blending method is 150 to 250°C. Preferably, the time of the melt blending method is 10 to 30 minutes. Preferably, the rotation speed of the melt blending method is 50 to 100 rpm. Preferably, the blending further includes extrusion molding; the thickness of the extrusion molding is 0.05 to 10 mm.
[0040] In the present invention, the parameters such as temperature, time and rotation speed of the melt blending method are optimized to ensure that the materials can be fully mixed during the blending process and avoid the degradation of material properties due to overheating. The temperature of the melt blending method is controlled within the range of 150 to 250°C, which can ensure that polylactic acid and other materials are fully flowed and mixed in a molten state to form a uniform blend. The blending time is controlled within 10 to 30 minutes to ensure that there is enough time for the raw materials to interact physically and chemically, thereby achieving the desired modification effect. The rotation speed is controlled within 50 to 100 rpm to ensure that the shear force during the mixing process is moderate, which can promote the dispersion and mixing of the raw materials without causing excessive shear damage to the materials.
[0041] In the present invention, the extrusion molding step is performed after blending, and the purpose is to further process the blend into a desired shape and size. The thickness of the extrusion molding is controlled at 0.1 to 10 mm, which can meet the requirements of material thickness in different application fields. Through extrusion molding, a modified polylactic acid material with a specific shape and size can be obtained, which is convenient for subsequent processing and application.
[0042] The present invention also provides the use of the toughened modified polylactic acid material or the toughened modified polylactic acid material prepared by the above preparation method in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing.
[0043] The application of the toughened modified polylactic acid material of the present invention in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing can provide excellent mechanical properties and low-temperature toughening effects, while having the advantages of environmental protection and sustainable development. For example, in automobile manufacturing, the material can be used to manufacture interior trims, body parts, etc., which not only reduces the weight of the vehicle, but also reduces the impact on the environment. In the field of aerospace, the material can be used to manufacture lightweight, high-strength structural parts to improve the performance of aircraft. In electronic equipment manufacturing, the material can be used to manufacture parts such as housings and brackets, providing good impact resistance and durability. In industrial equipment manufacturing and packaging material manufacturing, the material can provide environmentally friendly, degradable substitutes to reduce the pollution of plastic waste to the environment.
[0044] The application of the present invention in automobile manufacturing is preferably used to manufacture automobile shells, interior trims, suspension systems, engine parts, front-end modules, instrument panel frames, door modules, etc.
[0045] The application of the toughened modified polylactic acid material in aerospace is preferably used to reduce weight, thereby improving fuel efficiency and load capacity, making the aircraft lighter and more efficient, and to improve safety and protect internal electronic components from damage; used to enhance structural strength: the application of toughened plastics in aerospace structural parts, such as aircraft wings, fuselages, etc., can significantly improve the strength and toughness of the structure and reduce the risk of damage caused by external impact.
[0046] The application of the toughened modified polylactic acid material in electronic devices is preferably used to enhance the mechanical properties of electronic devices and reduce the risk of damage to the devices when subjected to external impact, such as mobile phone protective cases and headphone cables, which can effectively buffer the impact force and reduce the damage to the devices caused by falling or collision; used to improve safety and prevent wear and tear; used to extend the service life of electronic devices, effectively protect internal wires from the influence of the external environment, and ensure the long-term stability and safety of the equipment
[0047] The application of the toughened modified polylactic acid material of the present invention in the manufacture of industrial appliances is preferably to increase the environmental performance and service life of the appliances.
[0048] The application of the toughened modified polylactic acid material of the present invention in the manufacture of packaging materials is preferably to improve brittleness: significantly reduce the brittleness of the packaging material, so that it is not easy to break during transportation and storage, and extend the service life; improve impact resistance: when subjected to external force impact, it can absorb more energy to prevent the packaging material from breaking and protect the internal items from damage; enhance durability: the packaging material can still maintain good physical properties after repeated use, reduce the frequency of replacement, and reduce the overall cost; improve safety: it is not easy to break when subjected to impact, reduce the safety hazards caused by the rupture of the packaging material, and ensure user safety.
[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0050] Example 1
[0051] Weigh the following raw materials by weight and mix them evenly:
[0052]
[0053] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a toughened modified polylactic acid material.
[0054] The blended material was transferred to a single screw extruder for extrusion molding, and the thickness was set to 0.5 mm, and used as a sample for performance testing.
[0055] Example 2
[0056] Weigh the following raw materials by weight and mix them evenly:
[0057]
[0058] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 180° C. for 20 min to obtain a toughened modified polylactic acid material.
[0059] The blended material was transferred to a single screw extruder for extrusion molding, and the thickness was set to 0.5 mm, and used as a sample for performance testing.
[0060] Example 3
[0061] Weigh the following raw materials by weight and mix them evenly:
[0062]
[0063] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 220° C. for 20 min to obtain a toughened modified polylactic acid material.
[0064] The blended material was transferred to a single screw extruder for extrusion molding, and the thickness was set to 0.5 mm, and used as a sample for performance testing.
[0065] Example 4
[0066] Weigh the following raw materials by weight and mix them evenly:
[0067]
[0068]
[0069] All raw materials were put into an internal mixer for melt blending at a speed of 150 rpm and a temperature of 220° C. for 10 min to obtain a toughened modified polylactic acid material.
[0070] The blended material was transferred to a single screw extruder for extrusion molding, and the thickness was set to 0.5 mm, and used as a sample for performance testing.
[0071] Example 5
[0072] Weigh the following raw materials by weight and mix them evenly:
[0073]
[0074] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a toughened modified polylactic acid material.
[0075] The blended material was transferred to a single screw extruder for extrusion molding, and the thickness was set to 0.5 mm, and used as a sample for performance testing.
[0076] Comparative Example 1
[0077] Weigh the following raw materials by weight and mix them evenly:
[0078]
[0079] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a toughened modified polylactic acid material.
[0080] The blended material was transferred to a single screw extruder for extrusion molding, and the thickness was set to 0.5 mm, and used as a sample for performance testing.
[0081] Comparative Example 2
[0082] Weigh the following raw materials by weight and mix them evenly:
[0083]
[0084] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a toughened modified polylactic acid material.
[0085] The blended material was transferred to a single screw extruder for extrusion molding, and the thickness was set to 0.5 mm, and used as a sample for performance testing.
[0086] Comparative Example 3
[0087] Weigh the following raw materials by weight and mix them evenly:
[0088]
[0089] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a toughened modified polylactic acid material.
[0090] The blended material was transferred to a single screw extruder for extrusion molding, and the thickness was set to 0.5 mm, and used as a sample for performance testing.
[0091] Comparative Example 4
[0092] Weigh the following raw materials by weight and mix them evenly:
[0093]
[0094] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a toughened modified polylactic acid material.
[0095] The blended material was transferred to a single screw extruder for extrusion molding, and the thickness was set to 0.5 mm, and used as a sample for performance testing.
[0096] Comparative Example 5
[0097] Weigh the following raw materials by weight and mix them evenly:
[0098]
[0099] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a toughened modified polylactic acid material.
[0100] The blended material was transferred to a single screw extruder for extrusion molding, and the thickness was set to 0.5 mm, and used as a sample for performance testing.
[0101] The following tests were performed using pure PLA, materials obtained in Examples 1 to 5, and Comparative Examples 1 to 5 as samples:
[0102] Mechanical properties test:
[0103] Use a universal mechanical properties tester to test the tensile properties of the specimens and record the results;
[0104] The sample size is 4mm×1mm, the chuck spacing is 30mm, and the tensile speed is 5mm / min.
[0105] The samples were placed at room temperature for 48 hours before testing.
[0106] The tensile elastic modulus is tested during the tensile test. During the elastic deformation stage of the tensile test, the strain value of the sample under a specific stress is measured and the tensile elastic modulus is calculated using Hooke's law:
[0107] E = σ / ε, where E is the tensile elastic modulus, σ is stress, and ε is strain
[0108] The measurement results are shown in Table 1 below:
[0109] Table 1 Mechanical properties test results
[0110]
[0111]
[0112] It can be seen from the results that the polylactic acid material provided by the present invention is superior to pure PLA and the materials in the comparative examples in terms of elongation at break, tensile strength and tensile elastic modulus. The materials of Examples 1 to 5 have significantly improved elongation at break, achieving significant progress compared to pure PLA. In terms of tensile strength, the materials of the examples also show higher strength, which is significantly better than the comparative examples.
[0113] Impact toughness test:
[0114] The cantilever beam impact tester detects the impact toughness of the specimen and records the results;
[0115] The sample specifications are 80mm×10mm×4mm, the impact energy is 5.5J, the pendulum pre-lift angle is 150°, and the impact speed is 3.5m / s.
[0116] The samples were placed at room temperature for 48 hours before testing.
[0117] The measurement results are shown in Table 2 below:
[0118] Table 2 Impact toughness test results
[0119]
[0120]
[0121] As shown in Table 2, the polylactic acid material provided by the present invention is superior to pure PLA and the materials in the comparative example in terms of impact toughness. The materials in Examples 1 to 5 have significantly improved impact toughness compared to pure PLA. The materials in the examples show higher impact toughness, which is significantly better than the comparative example.
[0122] Referring to GB / T 1038-2000 Test Method for Gas Permeability of Plastic Film and Sheet, the gas permeability of the materials prepared in Examples 1 to 5 and Comparative Examples 1 to 5 was tested by pressure difference method, with a sample area of 20 cm 2 The measurement results are shown in Table 3 below:
[0123] Table 3 Air permeability test results
[0124]
[0125] As shown in Table 3, the material provided by the present invention has achieved remarkable results in reducing its air permeability, and its air permeability has been reduced to 6.23μm / Pa·s. This data shows that the molecular structure of the material is very tight, making it difficult for gas molecules to penetrate. It is precisely because of this unique molecular structure that the polylactic acid material in the present invention performs well in blocking gas and moisture and has broad application prospects. In particular, its application value is particularly significant in the fields of packaging and building materials.
[0126] In the field of packaging, the polylactic acid material of the present invention can effectively maintain the gas balance inside the package, thereby inhibiting the growth of microorganisms. In this way, the shelf life of food and other products can be extended, and the freshness of food can be better maintained. In addition, due to its excellent barrier properties, the material can also be used to manufacture various packaging containers, such as food packaging bags, cling film, etc., thereby providing consumers with safer and more hygienic packaging solutions.
[0127] In terms of building materials, the polylactic acid material of the present invention also has important application value. Due to its excellent barrier properties, the material can reduce the changes of building materials in the air, thereby improving its durability. In this way, the service life of the building materials is extended and the maintenance cost is correspondingly reduced. In addition, the material can also be used to manufacture various building components, such as roof tiles, exterior wall panels, etc., thereby providing the construction industry with more environmentally friendly and energy-saving building materials.
[0128] Therefore, the material provided by the present invention has achieved remarkable results in reducing gas permeability, and its molecular structure is compact, making it difficult for gas molecules to penetrate. This property makes the polylactic acid material of the present invention perform well in blocking gas and moisture, and has broad application prospects. Whether in the field of packaging or the field of building materials, the material of the present invention can provide excellent performance, thereby bringing more innovation and progress to related industries.
[0129] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A toughened and modified polylactic acid material, characterized in that: Made from the following raw materials in parts by weight:
2. The toughened modified polylactic acid material according to claim 1, characterized in that: Made from the following raw materials in parts by weight:
3. The method for preparing the toughened modified polylactic acid material according to claim 1 or 2, characterized in that: The following steps are involved: All materials are blended to obtain toughened modified polylactic acid material.
4. The method for preparing the toughened modified polylactic acid material according to claim 3, characterized in that: The blending is carried out by melt blending.
5. The method for preparing the toughened modified polylactic acid material according to claim 4, characterized in that: The equipment used in the melt blending method is an internal mixer.
6. The method for preparing the toughened modified polylactic acid material according to claim 4, characterized in that: The temperature of the melt blending method is 150-250°C.
7. The method for preparing the toughened modified polylactic acid material according to claim 4, characterized in that: The time of the melt blending method is 10 to 30 minutes.
8. The method for preparing the toughened modified polylactic acid material according to claim 4, characterized in that: The rotation speed of the melt blending method is 50-100 rpm.
9. The method for preparing the toughened modified polylactic acid material according to claim 3, characterized in that: The blending further includes extrusion molding; The thickness of the extrusion molding is 0.05-10 mm.
10. Use of the toughened modified polylactic acid material according to claim 1 or 2, or the toughened modified polylactic acid material prepared by the preparation method according to any one of claims 3 to 9 in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing.
Citation Information
Patent Citations
Polylactic acid flexibilizer and preparation method thereof and modified polylactic acid and preparation method thereof
CN102675523B
Modification method for strengthening and toughening polylactic acid material
CN110204876A